Tuning the Thermoelectric Performance of Hybrid Tin Perovskites by Air Treatment. Issue 2 (11th November 2020) - Haque, Md Azimul; Hernandez, Luis Huerta; Davaasuren, Bambar; Villalva, Diego Rosas; Troughton, Joel; Baran, Derya
Abstract : The intriguing properties of halide perovskites have led to high‐performance optoelectronic devices. Recently, tin (Sn) halide perovskites have attracted significant interest for thermoelectrics due to their high electrical conductivity and low thermal conductivity. Herein the thermoelectric performance of Sn and binary tin–lead (Sn–Pb) hybrid perovskites is evaluated. Leveraging the oxidative nature of Sn, air treatment of the perovskite films leads to improved thermoelectric performance due to self‐doping. The film conductivity increases significantly with a semiconductor to quasi‐metallic transition upon air exposure. In addition, this enhanced electrical conductivity is preserved after controlled air exposure for extended period of time. An increase of 42% and 83% in the thermoelectric power factor of CH3 NH3 SnI3 and CH3 NH3 Sn0.75 Pb0.25 I3 is observed, respectively, after air treatment compared to pristine films at 336 K. Apart from thermoelectrics, the implications of this work are relevant to other perovskite devices such as solar cells and light‐emitting diodes (LEDs). Abstract : Understanding electronic instability and oxidative behavior of Sn perovskites is crucial for their further development as a thermoelectric material. Herein, a simple strategy of air treatment is used to enhance the thermoelectric performance of hybrid tin perovskites.